The Capital Structure Decisions of New Firms - Robb, Alicia M.; Robinson, David T. (Review of Financial Studies, 2014)
We study capital structure choices that entrepreneurs make in their firms' initial year of operation, using restricted-access data from the Kauffman Firm Survey. Firms in our data rely heavily on external debt sources, such as bank financing, and less extensively on friends-and-family-based funding sources. Many startups receive debt financed through the personal balance sheets of the entrepreneur, effectively resulting in the entrepreneur holding levered equity claims in their startups. This fact is robust to numerous controls, including credit quality. The reliance on external debt underscores the importance of credit markets for the success of nascent business activity.